Impact of earnings per share and dividend per share on firm value - Muryani Arsal (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The purpose of this study is to explore the impact of earnings per share (EPS) and dividends per share (DPS) on the value of the company on the Indonesian stock exchange for the period 2014-2017. This study uses data from 6 food industry companies listed on the Indonesian Stock Exchange to examine the impact of these variables. Multiple regression models are used to determine the effect of earning per share and dividend per share. The results of the research show that earnings per share separately have a significant and positive impact on company value. However, the dividend per share does not substantially affect the value of the company. The findings of this research also found that firm value is affected simultaneously by EPS and DPS. The study concludes that investors can use Earnings per Share as the basis for making investment decisions, particularly on the Indonesian Stock Exchange for companies in the food industry. In practical terms, the implications of this research indicate that the management of companies listed on the Stock Exchange must formulate a dividend policy and develop a company strategy aimed at internal and external factors in order to increase the value of the company.